Respuesta :
The problem is set equal to zero. (x+4)(x+10)=0 Therefore, x= -10, x= -4
Answer:
The solutions are
-4 and -10
Step-by-step explanation:
We are given a quadratic equation in terms of variable x as follows:
[tex]x^2+14x+40=0[/tex]
We may solve this question by using the method of splitting the middle term in order to find the value of x from the equation.
The given equation could be written as:
[tex]x^2+10x+4x+40=0[/tex]
Now on taking out the common terms in pair we get:
[tex]x(x+10)+4(x+10)=0\\\\(x+4)(x+10)=0[/tex]
Hence, we get:
[tex]x=-4\ and\ x=-10[/tex]